The Effect Of Training And Work Motivation On Employee Performance At PT Gos Indoraya Tangerang - Anwar, Samsul; Sudarso, Aden Prawiro (Pascasarjana Universitas Pasundan, 2025)
This study aims to determine the effect of Training and Work Motivation on Employee Performance at PT GOS Indoraya Tangerang. This study uses quantitative research with an associative method approach. The population in this study were all employees at PT GOS Indoraya Tangerang. In this study, the sampling used was saturated sampling of 56 respondents. Data collection was by questionnaire. The data analysis method used simple linear regression test, multiple linear regression, correlation coefficient, determination coefficient, partial t test and simultaneous F test. The results of the study showed that: Training has a positive and significant effect on employee performance at PT GOS Indoraya Tangerang. This can be proven from the simple linear regression equation Y = 9.650 + 0.250X1. The correlation value of 0.464 is moderate (quite strong). The determination coefficient value is 21.6%. The calculated t value is 3.852 > t table 2.004 with a significance of 0.001 < 0.05. Work motivation has a positive and significant effect on employee performance at PT GOS Indoraya Tangerang, this can be proven from the simple linear regression equation Y = 9.469+0.24X2. The correlation value is 0.415, which is moderate (quite strong). The coefficient of determination is 17.2%. The calculated t value is 3.351 > t table 2.004 with a significance of 0.001 < 0.05.Simultaneously, Training and Work Motivation have a positive and significant effect on employee performance at PT GOS Indoraya Tangerang, this can be proven from the multiple linear regression equation Y = 6.927 + 0.203X1 + 0.185X2, the correlation value is 0.593 (Strong Enough). The coefficient of determination is 30.2%. The Fcount value is 11.487 > Ftable 4.01 with a significance level of 0.001 < 0.05.